Impacto do crédito bancário no crescimento econômico brasileiro entre os anos de 2005 e 2016 - Borrasca, Clodemar Rubens (Universidade do Vale do Rio dos Sinos, 2022)
Governmental entities must seek the well-being of population and the economic growth is a variable that can provide it. Therefore, understanding the relation between the expansion of bank credit and the variation of GDP has its empirical relevancy, especially to provide less poverty and misery, and better quality of life. The relation between credit offer and product growth is being studied through a theory known as "finance-growth nexus", which precognizes the quality and relation between financial development and economic growth, using the aggregated credit as interest variable and representing the financial intermediation (KING e LEVINE, 1993); BECK et al., 2000; KOOP et al., 2000; LEVINE, 2005; BECK et al.; 2014b). This study sought to identify empirically the relation between bank credit and economic growth in Brazil, in the timespan of 2005 to 2016. To reach this goal, three hypothesys of the individual relation between the explained variables of total aggregated credit, individual credit and corporate credit, with the GDP as a dependent variable using socioeconomical variables as control. The sample is unprecedented, extracted from reports from the Central Bank of Brazil (Banco Central do Brasil), composed of regional data separated by zip code (CEP), with pannel data being used as data model. The results show a positive association between bank credit and GDP per capita. The results of the hypothesys H2, that refers to the impact of the individual credit on the GDP, is constitued of an unprecedented contribution on this field. While prior investigations obtained negative correlation, this study confirmed a positive correlation between individual credit and growth of the GDP. This conclusion can contribute to the theory, because (BECK et al., 2014; JAPELLI e PAGANO, 2014; SASSI e GASMI, 2014; LEON, 2016) present strong evidence of a negative relation of individual credit and the growth of GDP. This information is relevant and contributes to the development of the theory, as it can be associated with the massive individual credit expansion seen in the last decades, and, with the end of the hyper-inflationary period, makes possible the direct credit for the consumer, the housing financing, durable goods and vehicles, besides the development of payroll loans attached to the yields of individual credit. More so, with the robustness test, it was aggregated an unprecedented variable, which englobes the corporate credit and the resources allocated in housing credit and agricultural credit, therefore contributing with the result of the hypothesys structured ex ante.
Keywords: Desenvolvimento financeiro; Crédito bancário; Crescimento econômico; Financial development; Bank credit; Economic growth; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis